Análisis crítico del uso de macroinvertebrados bentónicos como bioindicadores de la calidad del agua en el Sistema Nacional de Gestión Ambiental - Lazo Oscanoa, Carlos Alberto (2022)
Due to the worrisome water context at domestic and global level, it is imperative to establish actions for protecting and conserving aquatic ecosystems and water resources in Peru, such as establishing a comprehensive assessment of water quality. In this context, bio indicators, especially benthic macroinvertebrates, represent an important tool for efficient water assessment. This essay analyzes how the use of these bio indicators is being managed at international level and within the framework of the National Environmental Management System (SNGA) of Peru, with special emphasis on the National Water Resources Management System (SNGRH), since one of its objectives is to achieve an adequate management of water resources in the country, to contribute to the conservation, preservation and recovery of water and its associated goods, and to have the conservation and protection of water quality as one of its purposes. In this way, it was evident that these bio indicators are being considered in some of the SNGA management instruments. However, in some of these, their use is not very developed or is limited because they do not have a strong legal basis, since they have not yet been incorporated in the regulatory framework of water resources and, therefore, in the protocols that address their use.